Analisis Komparatif Pendapatan Pengolah Kopra Hitam dengan Pengolah Kopra Putih di Desa Horongkuli Kecamatan Toari Kabupaten Kolaka - Pranata, Khafidzi; Yunus, Lukman; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
Black copra processor with white copra In Horongkuli Village, Toari District, Kolaka Regency is a form of processing or post-harvest handling for coconuts, this is related to the purpose of processing black copra and white copra to further increase the sale value of their plantation products to obtain more income. The purpose of this study is to (1) determine the magnitude of black copra and white copra processor income (2) know whether there are differences in the acquisition of black copra and white copra processors (3) Know the business efficiency of processing black copra and white copra. The analytical method used in this study is income analysis, efficiency analysis, and T-test. Based on the results of the research, the amount of black copra and white copra processing income is Rp. 3,604,333 and Rp. 5,790,067. Both of these businesses are classified as efficient. costs are 2.63 and 2.92 (ratio> 1) while the T-Test results of black copra and white copra processing income of count of 3.106> t table of 2.048 means that there is a difference in income.